Americanization in the conditional: Brazil in the 40ths - Tota, Antonio Pedro (Universidade Estadual Paulista / UNESP, 2007)
The main issue of this paper is to demonstrate the roots of a process that can be called the "americanization" of the Brazilian society. Through radio programmes, movies, cartoons and any other cultural manifestation, the Office of the Coordinator of Inter American Affairs succeeded in spreading a very good image of the USA in Brazil so that it could have the Pan-American union-against the Axis.